The effects of grammatical proscription on morphosyntactic change: Auxiliary variation in Franco-American French - Stelling, Louis (Arborescences, 2011)
The author explores the influence of grammatical proscription on morphosyntactic change (or lack thereof) in two Franco-American communities, based on data gathered through sociolinguistic interviews with French-English bilinguals from Southbridge, Massachusetts and Woonsocket, Rhode Island. A study of the use of passé composé shows that although a great deal of variation exists within the communities, language shift does not appear to be causing rapid linguistic change. The author also finds that, with the exception of community of residence, every social constraint considered was found to exercise a significant influence on variation. The analysis thus indicates that despite the sociolinguistic situation of language shift, the passé composé shows a high degree of resistance to grammatical simplification in both Southbridge and Woonsocket.